The Concept of Authoritarian Leadership in Madrasah Tsanawiyah (MTs) Al-Hakim Sukabumi - Dede Nurhasanah; Rita Alfin; Abiyyu Naufal Malik; Mulyawan Safwandy Nugraha (International Journal of Management Science, 2023)
The purpose of this research is to analyze the concept of authoritarian leadership style at Mts Al-Hakim Sukabumi. This type of research is a case study of research in the field using primary data sources obtained through direct interviews. In addition, data was obtained through literature study using secondary data sources which were summarized and collected from laws, websites, books, e-books and other sources that were highly relevant to the research problem discussed. The data of this research were analyzed qualitatively and interactively, starting from data collection, reduction, presentation, and drawing conclusions. The results of this study illustrate that the concept of leadership style at Mts Al-Hakim Sukabumi is divided into 4 types, namely intimidation, reflection, adaptation, and reaction. The recommendation of this research is that the principal is expected to have a more appropriate and adaptive application of his leadership style. Furthermore, for other researchers, it is suggested to expand the research by including other literature or other methods based on leadership style to further explore what concepts and factors are related to the principal's leadership style.